Decomposition of productivity growth of the Malaysian Manufacturing Sector, 1983-2005 - Noorasiah Sulaiman; Zakariah Abdul Rashid (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present paper examines the productivity growth of Malaysian manufacturing industries between 1983 and 2005. Unlike previous studies that use one source of data, the present study uses two sources of data:the Malaysian Input- Output Tables and the Malaysian Industrial Manufacturing Survey. The analysis focuses upon on the decomposition of aggregate total factor productivity (TFP) growth into three effects: technical change, linkage and final demand. The findings indicate that final demand is the largest contributor to growth in overall TFP. In addition, a small contribution stems from technical change and particularly linkage effects. When the decomposition of final demand effect is extended into price and real share effects, the findings obtained demonstrate that a change in relative prices significantly influences the change in output share produced.